THE INFLUENCE OF BLOOD VOLUME AND STORAGE DURATION ON THE ERYTHROCYTE SEDIMENTATION RATE (ESR) VALUE USING THE WESTERGREN METHOD - Inna Marlina; Eem Hayati; Adang Durachim; Zuri Rismiarti; Ganjar Noviar (Journal of Vocational Health Studies, 2025)
Background: Hematological examination is conducted to determine the condition of blood and its components, which are used to establish a diagnosis, support a diagnosis, make a differential diagnosis, monitor disease progression, assess the severity of an illness, and determine the initial prognosis of a disease. Phlebotomy procedures in the pre-analytical stage are not always successful and sometimes encounter failure. Inappropriate anticoagulant administration can lead to erroneous hematological examination results, including Erythrocyte Sedimentation Rate (ESR) examination results. Purpose: This research aims to examine the influence of blood volume and storage duration on the Erythrocyte Sedimentation Rate (ESR) value using the Westergren method. Method: The Westergren method utilizes 5 venous blood samples with a ratio of blood volume to 3.8% anticoagulant at 4 : 1, 3 : 1, and 2 : 1, with sample storage durations of 0 and 3 hours at room temperature. Result: The average ESR values with a ratio of 4 : 1, at 0 hours, were 5.20 mm/hour and at 3 hours were 3.60 mm/hour. The average ESR values with a ratio of 3 : 1, at 0 hours, were 6.20 mm/hour and at 3 hours were 4.40 mm/hour. The average ESR values with a ratio of 2 : 1, at 0 hours, were 7.60 mm/hour and at 3 hours were 5.60 mm/hour. Conclusion: There is a significant influence of blood volume (p-value < 0.05) and storage duration (p-value = 0.05) on the Erythrocyte Sedimentation Rate (ESR) value using the Westergren method.